Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

(ii) 2x – 1/6 = 3 (ii) 2x – 1/6 = 3 (ii) 2x – 1/6 = 3 (ii) 2x – 1/6 = 3 (ii) 2x – 1/6 = 3 (ii) 2x – 1/6 = 3

(ii) 2x – 1/6 = 3
(ii) 2x – 1/6 = 3
(ii) 2x – 1/6 = 3
(ii) 2x – 1/6 = 3
(ii) 2x – 1/6 = 3
(ii) 2x – 1/6 = 3

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5733 Points
5 months ago
Dear Student

2x – 1/6 = 3

2x = 3 + 1/6

2x = 19/6

x = 19/12

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free